Sensitivity-analysis based method in single-robot cells cost-effective design and optimization. (April 2016) - Zhang, Jiafan; Fang, Xinyu; Qi, Liwei
Abstract: Robot-centered cells play increasingly important roles in corporate automation and repetitive processing to improve productivity and quality. How to provide an optimal robotic cell design either from cost-effectiveness or from productivity enhancement is a highlighted objective, especially in 3C industry of communication, computer and consumer electronics where the cost is always sensitive. Although, in the past years, several optimizing solutions have been achieved, the robotic cell optimization is still an open question both in industry and academia, due to the diversities of cell patterns determined by some main factors as single/dual gripper, simple/parallel workstation, and so on. This work targets the optimization design of a single-robot cell from cost-effective viewpoint, by means of the sensitivity analysis, performed in terms of the processing time, the traveling time and the gripper configuration. It provides an indication on the relationship between the cell productivity and the main factors. By comparing the resulting increase in revenue with the additional equipment costs, it intuitively provides the optimal solution by considering the gripper type, and whether or how many parallel workstations are needed. A demonstration to enhance the productivity of a single-robotic cell from real-life engineering scenario is performed with an encouraging result. Highlights: The paper considers the design of an economically efficient robotic cell, parallel workstations at each production stage, gripper type of the robot, and the layout, which affects the travel time of the robot. This proposed method is successfully employed in the real-life engineering cases by ABB engineers. Its effectiveness are fully demonstrated by these established engineering scenarios.